2016
DOI: 10.1007/s10943-016-0328-2
|View full text |Cite
|
Sign up to set email alerts
|

Revalidation of the Sat-Chit-Ananda Scale

Abstract: Sat-Chit-Ananda is an indigenous construct that refers to absolute bliss and consciousness. The present study aimed to strengthen the psychometric properties of the newly developed Sat-Chit-Ananda scale (Singh et al. in Int J Vedic Found Manag 1(2):54-74, 2014). A total of 398 students aged 17-36 years (mean age = 21.33 years, SD = 2.2, 70% males) participated in this study. An exploratory as well as confirmatory factor analysis was computed for the 17-item scale. Its' concurrent validity was established by as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…That factor encompassed items assessing energy, initiative, standing up for oneself, challenges in dealing with difficult people, and ways to achieve what you want to achieve. Sat-Chit-Ananda Scale scores have shown positive correlations with satisfaction with life, subjective happiness and flourishing, peace of mind, harmony in life, and experiences of positive emotions, and they have shown inverse correlations with experiences of negative emotions (Singh et al, 2014b(Singh et al, , 2018.…”
Section: Using Scales To Assess Key Indian Constructs: Strengths and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…That factor encompassed items assessing energy, initiative, standing up for oneself, challenges in dealing with difficult people, and ways to achieve what you want to achieve. Sat-Chit-Ananda Scale scores have shown positive correlations with satisfaction with life, subjective happiness and flourishing, peace of mind, harmony in life, and experiences of positive emotions, and they have shown inverse correlations with experiences of negative emotions (Singh et al, 2014b(Singh et al, , 2018.…”
Section: Using Scales To Assess Key Indian Constructs: Strengths and ...mentioning
confidence: 99%
“…In some studies, overall well-being has been operationalized as sat-cit-ānanda, which is traditionally understood as a natural state of every human being that involves inner happiness, bliss, and well-being-an emancipated state that every human strives to achieve (see Rao & Paranjpe, 2016;Singh et al, 2014b). In developing a 17-item Sat-Cit-Ānanda Scale, Singh et al (2014b) found evidence that sat-cit-ānanda is comprised of cit (or chit, consciousness), antaḥśakti (or antahshakti, inner strength), sat (truthfulness), and ānanda (bliss). These revealed factors indicated that cit or consciousness relates to taking responsibility for one's thoughts, emotions, speech, feelings, and actions.…”
Section: Using Scales To Assess Key Indian Constructs: Strengths and ...mentioning
confidence: 99%
“…In some studies, overall well-being has been operationalized as sat-cit-ānanda, which is traditionally understood as a natural state of every human being that involves inner happiness, bliss, and well-being-an emancipated state that every human strives to achieve (see Rao & Paranjpe, 2016;Singh, Khari, et al, 2014). In developing a 17-item Sat-Cit-Ānanda Scale, Singh, Khari, et al (2014) found evidence that sat-cit-ānanda is comprised of cit (or chit, consciousness), antaḥśakti (or antahshakti, inner strength), sat (truthfulness), and ānanda (bliss).…”
Section: Using Scales To Assess Key Indian Constructs: Strengths and ...mentioning
confidence: 99%
“…Ānanda or bliss refers to the state of mind when an individual ceases to be afflicted by reactivity to the thoughts, behaviors, and actions of others. (Singh, Khari, et al, 2014;Singh et al, 2018).…”
Section: Using Scales To Assess Key Indian Constructs: Strengths and ...mentioning
confidence: 99%
“…In this level, individuals have a sense of complete serenity and fulfillment in combination with freedom and peace [16]. In other words, they are fully responsible of their thoughts, speech, feelings and actions [52].…”
Section: Upper-level Of Consciousness Statementioning
confidence: 99%